A novel approach to fabricate fully biodegradable poly(butylene succinate) biocomposites using a paper-manufacturing and compression molding method. (December 2020) - Zhao, Liang; Huang, Hao; Han, Qianqian; Yu, Qiao; Lin, Panlong; Huang, Shiqi; Yin, Xianze; Yang, Feihua; Zhan, Jiayu; Wang, Hua; Wang, Luoxin
Abstract: In this work, a fully biodegradable poly(butylene succinate) (PBS) biocomposite was fabricated from ultrafine PBS fiber and waste paper (WP) using a paper-manufacturing and compression molding method. A PBS biocomposite containing 60 wt% WP showed a tensile strength, elongation at break, flexural strength, flexural modulus, interlaminar shear strength (ILSS), and impact strength of 78.1 MPa, 11.1%, 92.0 MPa, 7.5 GPa, 2.9 MPa, and 36.9 kJ/m 2, respectively, which were superior to those of previously-reported PBS biocomposites. The damage mechanics reveals that tremendous deformation of plant fibers (PF) from WP and their riveting improved the mechanical properties of WP/PBS biocomposites. The weight loss ratio of WP/PBS-60 wt% biocomposite during biodegradation reached 95.1 wt% after immersion in an enzyme solution for 35 d. This fabrication approach provides a novel and facile strategy to develop high-performance, low-cost, and fully biodegradable PBS biocomposites.